DDL-920 mediated enhancement of γ-oscillations targeting γ-aminobutyric acid receptors: a novel therapeutic strategy to improve cognition in Alzheimer's disease - Ali Aamir; Hafiza Hafsa (Neurology Letters, 2025)
Alzheimer's disease (AD) is the leading cause of dementia and poses significant health challenges globally. Characterised by cognitive decline and neurodegenerative pathology, including neurofibrillary tangles and amyloid plaques, AD currently lacks effective treatments that halt its progression. This article explores a novel therapeutic approach using DDL-920, a small molecule that enhances gamma oscillations by targeting γ-aminobutyric acid type A receptors (GABAARs), thereby improving cognitive function independent of amyloid and tau pathology. Preclinical studies demonstrate that DDL-920 enhances endogenous gamma oscillations, crucial for higher-order cognitive functions, in AD mouse models. Unlike traditional therapies focusing on amyloid clearance, DDL-920 shifts the focus to enhancing brain activity. While current treatments primarily manage symptoms, DDL-920's unique mechanism may offer a new avenue for cognitive improvement. However, the translation of its efficacy to human populations remains uncertain due to individual variability in brain rhythms and the complexity of neurodegeneration. Further research, including human trials, is essential to assess the long-term viability and scalability of DDL-920 as a therapeutic option for AD.